COMPARING THE EFFICACY OF 4 MG VS 2 MG INTRAVITREAL TRIAMCINOLONE ACETONIDE IN THE TREATMENT OF DIFFUSE DIABETIC MACULAR EDEMA - AADIL, N; WAQAS, HM; FATIMA, M; KHAN, SS (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in the Department of Ophthalmology from January 2022 to January 2023 to compare the effectiveness of two doses of TA on DME using central macular thickness (CMT) as the primary criterion. A total of 30 patients were included in the study. Participants were randomly divided into a 4mg TA group (n=16) and a 2 mg TA group(n=16). The injection was given in the eye with higher CMT. Patients were followed up until 6 months after injection. Results showed that regarding mean CMT and change in macular thickness, there was no statistically significant difference between both groups during the whole study period. After 1 month of injection, the ETDRS score in the 4 mg group increased significantly from 37.7±14.1 to 51.3±14.3 (P=0.0012) and from 41.9± 13.3 to 49.4± 13.7 in the 2mg group (P=0.002). Based on the results it can be concluded that the intravitreal 2 mg or 4 mg TA injection had a similar effect on both VA and CMT in patients with DME.